Impacts and Consequences of Digital Democratic Innovations in Political Parties - Gema Sánchez Medero; Rubén Sánchez Medero (Colombia Internacional, 2025)
Objective/context: In recent years, political parties have undergone significant transformation by adopting digital tools aimed at increasing member engagement and participation in internal processes. Digital democratic innovations have emerged as a key response to the crisis of legitimacy and declining membership facing traditional parties. This article offers a comprehensive overview of the main digital democratic innovations implemented by political parties, analyzing their forms—such as online platforms, digital primaries, fundraising, and deliberative spaces—and their impact on intraparty democracy. Methodology: Using a descriptive-analytical approach, the article first clarifies the concepts of democratic and digital innovation and then systematically reviews the digital tools used by parties to open new channels for participation and decision-making. It also examines explanatory factors for digitalization, such as party age, size, ideology, and institutional context, and critically assesses the potential and limitations of these innovations. Conclusions: The democratization of political parties through digital means has produced mixed results, falling short of expectations. The article concludes with practical recommendations to enhance meaningful participation, transparency, and inclusivity in intraparty democracy. Originality: The originality of this study lies in its integrative mapping and critical analysis of recent digital democratic innovations in political parties, providing both a broad perspective and nuanced insights into their real-world impact.